The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/ic201006q
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Synthesis and Correlation between Structure, Magnetic, and Dielectric Properties in LiNbO3-Type MnMO3 (M = Ti, Sn)

Abstract: LiNbO(3)-type MnMO(3) (M = Ti, Sn) were synthesized under high pressure and temperature; their structures and magnetic, dielectric, and thermal properties were investigated; and their relationships were discussed. Optical second harmonic generation and synchrotron powder X-ray diffraction measurements revealed that both of the compounds possess a polar LiNbO(3)-type structure at room temperature. Weak ferromagnetism due to canted antiferromagnetic interaction was observed at 25 and 50 K for MnTiO(3) and MnSnO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 30 publications
(43 reference statements)
6
70
0
Order By: Relevance
“…16 The prediction is thereafter validated by the synthesis of the high-pressure form of LN-type FeTiO 3 which is ferroelectric at and below room temperature and weakly ferromagnetic below 120 K. 17 Lately, Inaguma et al 18 synthesized LN-type MnTiO 3 with space group R3c under high pressure and temperature. They investigated its properties and confirmed that this compound is also ferroelectric polar at room temperature and has weak ferromagnetism at 25 K. Recently, Shin et al 19 experimentally demonstrated a high ferroelectric polarization level of ;47 lC/cm 2 in the heteroepitaxial thin film of LN-type ZnSnO 3 following its synthesis using high-pressure method.…”
Section: Introductionmentioning
confidence: 96%
“…16 The prediction is thereafter validated by the synthesis of the high-pressure form of LN-type FeTiO 3 which is ferroelectric at and below room temperature and weakly ferromagnetic below 120 K. 17 Lately, Inaguma et al 18 synthesized LN-type MnTiO 3 with space group R3c under high pressure and temperature. They investigated its properties and confirmed that this compound is also ferroelectric polar at room temperature and has weak ferromagnetism at 25 K. Recently, Shin et al 19 experimentally demonstrated a high ferroelectric polarization level of ;47 lC/cm 2 in the heteroepitaxial thin film of LN-type ZnSnO 3 following its synthesis using high-pressure method.…”
Section: Introductionmentioning
confidence: 96%
“…The polar lattice distortion was recently predicted to induce weak ferromagnetism in spin-ordered LiNbO 3 -type ATiO 3 (A = Fe, Mn, and Ni) phases through the antisymmetric Dzyaloshinsky-Moriya (DM) exchange interaction, leading to a proposed mechanism for the electric field control of magnetization. 8 Coexistence of weak ferromagnetism and ferroelectricity in LiNbO 3 -type FeTiO 3 and magnetodielectric coupling in MnTiO 3 -II have subsequently been reported, 9,10 but the magnetic structures were not determined. We report here a neutron and magnetization study of the low temperature spin order in MnTiO 3 -II in zero and applied magnetic fields, leading to the discovery of an unusual low field domain reorientation which breaks the powder-averaging diffraction and allows an unambiguous determination of the spin directions.…”
Section: Introductionmentioning
confidence: 99%
“…Different from CaMnTi 2 O 6 , in polar ZnTiO 3 [22] or MnTiO 3 [24] the ν 2 [A 1 (2)] Raman mode vanishes in the first-order phase transition, while in CaMnTi 2 O 6 it stays and hardens as an indication of a less abrupt phase transformation. In fact, the behavior observed in CaMnTi 2 O 6 was previously reported in other pressure-induced second-order phase transitions [25] and indicates that even though the mode softening up to the phase transition is not driving the phase transition, it is sensitive to the motion of the ions involved in the transition process.…”
Section: B Raman Spectroscopymentioning
confidence: 98%
“…The largest coexisting ferroelectric and magnetic effects are found in type-I multiferroics, in which an ambient-temperature ferroelectric compound containing a magnetic ion shows an antiferromagnetic order at sufficiently low temperature. Unfortunately, while most type-I multiferroics have a large spontaneous polarization, they do not show bulk ferroelectricity due to their large leakage and coercive field [2]. Recently, Aimi et al [3] have discovered that CaMnTi 2 O 6 is a multiferroic with a moderate spontaneous polarization of ∼24 μC/cm 2 and the first example of an oxide containing Mn 2+ allowing a polarization reversal at ambient temperature, thus leading to a novel class of type-I multiferroics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation